Babymouse. [1], Queen of the world! - Holm, Jennifer L.; Holm, Matthew (New York : Random House, 2005)
An imaginative mouse dreams of being queen of the world, but will settle for an invitation to the most popular girl's slumber party.
Notable/Best Books (A.L.A.)
Publisher's Weekly
School Library Journal
2.8
3-6
3-6
Keywords: Animals -- Juvenile fiction; Friendship -- Juvenile fiction; Imagination -- Juvenile fiction; Mice -- Juvenile fiction; Popularity -- Juvenile fiction; Animals -- Fiction; Cartoons and comics; Friendship -- Fiction; Imagination -- Fiction; Mice -- Fiction; Popularity -- Fiction; Animals -- Fiction; Comic books, strips, etc; Friendship -- Fiction; Imagination -- Fiction; Mice -- Fiction; Popularity -- Fiction; Graphic novels